Characteristics of slow earthquakes in the very low frequency band: Application to the Cascadia subduction zone. Issue 8 (24th August 2016) - Ide, Satoshi
Abstract: Deep tectonic tremors detected in many subduction zones worldwide are often accompanied by very low frequency (VLF) signals, detectable by broadband seismometers but usually hidden in large ambient noise. By stacking broadband seismograms relative to tremor hypocentral times, we can recover the VLF signals. The stacked signals are then inverted to determine a moment tensor solution, using a procedure previously applied to VLF signals in Japan, Taiwan, and Mexico. Here we apply this method to the Cascadia subduction zone, where tremors and slow slip events are clearly observed. As expected, we successfully recover VLF signals for almost the entire tremor region beneath southern Vancouver Island and northern Washington State. The moment tensors are mostly well determined as low‐angle thrust type, but source depths are poorly constrained. The slip direction is slightly rotated counterclockwise with respect to the local plate motion direction, probably due to bending of the subducting plate. The seismic moment measured in VLF band is proportional to the seismic energy of tremors, with a scaled energy of about 3 × 10 −9 . The widespread observability of VLF signals suggests that the deformation associated with tremors and SSEs is actually a very broadband phenomenon, as suggested by stochastic models. Key Points: Focal mechanisms in VLF band are determined in the Cascadia subduction zone Low‐angle thrust focal mechanisms with slightly variable slip directions VLF signals are likely to be part of very broadband signals